2020
DOI: 10.5539/ijel.v11n1p192
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory and Confirmatory Factor Analyses of L2 Linguistic Complexity Measures

Abstract: This study investigated the latent structure of L2 linguistic complexity as a multidimensional construct and analyzed the relationship between the sub-constructs of L2 linguistic complexity by employing exploratory and confirmatory analyses of a set of linguistic complexity measures indexing different sources of L2 linguistic complexity. Based on relevant theories and empirical studies, 11 automated measures indexing distinct sources of syntactic and lexical complexity were selected and used to assess the ling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…With the application of an EFA, Yoon (2017) showed that (a) “lexical and morphological dimensions of complexity loaded on one construct” and (b) “the unit-length measures with different base units loaded on different constructs” (p.130). Also, Li and Zhang (2020) studied the latent structure of L2 linguistic complexity by using an EFA followed by a CFA in writing tasks from Chinese EFL students. A set of measures were included, including subordination measures, phrasal measures, lexical measures, and overall complexity measures.…”
Section: Introductionmentioning
confidence: 99%
“…With the application of an EFA, Yoon (2017) showed that (a) “lexical and morphological dimensions of complexity loaded on one construct” and (b) “the unit-length measures with different base units loaded on different constructs” (p.130). Also, Li and Zhang (2020) studied the latent structure of L2 linguistic complexity by using an EFA followed by a CFA in writing tasks from Chinese EFL students. A set of measures were included, including subordination measures, phrasal measures, lexical measures, and overall complexity measures.…”
Section: Introductionmentioning
confidence: 99%